Untangling business model innovation in family firms: Socioemotional wealth and corporate social responsibility perspectives - López-Nicolás, Carolina; Meroño-Cerdán, Ángel L.; Heikkilä, Marikka; Bouwman, Harry (Elsevier [Commercial Publisher], 2025)
Despite the increasing interest in business model innovation (BMI) as a way to improve the performance of firms, and the predominance of family firms (FFs) in modern economy, these two topics have so far not been combined. Drawing on socioemotional wealth (SEW) theory and the corporate social responsibility (CSR) concept, and on insights from research into BMI, we conduct a qualitative analysis using data from fifteen European FFs, examining the strategic and BM focus, the nature of the BM renewal, and the process and outcomes of BMI on their business models (BMs). Our results identify several BM configurations, with a focus on (1) growth by internationalization in combination with attention to increased quality in value creation, and (2) profit orientation based on increased efficiency, enabled by digitalization, mainly in the value delivery components of a BM. The latter reflects distinctive, innovative capabilities found in FFs, that contribute to the preservation of family objectives, as suggested by SEW theory and business orientation on CSR. Furthermore, there is a link between family involvement and limited, but specific, knowledge-related resources, and the way the dynamic BMI process is governed and executed.